Development of magnetic nanoparticles for biomedical devices - Pereira, Rute Alexandra Correia (2020)
In the last decades, magnetic nanoparticles have been developed for biomedical applications, such as medical treatment and imaging. In medical treatment, magnetic nanoparticles have been extensively used in hyperthermia, a treatment that requires the heating of cancer cells but lacks local temperature control, which often leads to damage in healthy cells. This thesis addresses this problem using Fe3Se4 nanoparticles that have a Curie temperature slightly above 40 °C. In medical imaging, the quest for contrast manipulation has been pursued during the last decades. The use of contrast agents is nowadays common when performing an MRI. These contrast agents are molecules, nanoparticles or compounds, that alter the magnetic environment and can later increase or decrease the contrast of the obtained image. Fe3Se4 nanoparticles here presented are also evaluated as contrast agents for MRI. In addition, the development of dual-mode contrast agents represents a new generation, which takes advantage of the two relaxation modes, allowing a higher contrast between healthy and unhealthy tissues. Regarding this, the present thesis also reports the development of a new synthesis approach to yield a dual-mode contrast agent that combines Fe3O4 nanoparticles and a Gadolinium based metal-organic complex. Synthesis and characterizations of all the nanoparticles and Gadolinium complexes are presented, as well as the ecotoxicological and cytotoxic evaluations of the nanoparticles